Analisis Keterwakilan Perempuan Sebagai Penyelenggara Pemilu 2024 (Studi Kasus Partisipasi Perempuan Sebagai Panitia Pengawas Pemilu Kecamatan di Kabupaten Ponorogo) - Bagaskara, Aldian; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The representation of women in electoral management bodies is a critical issue in achieving inclusive and gender-equitable democracy. Although national regulations such as Law No. 7 of 2017 and Bawaslu Regulation No. 4 of 2022 mandate a minimum 30% quota for women in election committees, implementation at the regional level remains challenging. This study aims to analyze the extent of women’s involvement in the District Election Supervisory Committees (Panwascam) during the 2024 General Election in Ponorogo Regency and to identify the barriers that hinder the fulfillment of the mandated quota. This research employs a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews, field observations, and document analysis. The analytical framework is based on Hanna Pitkin’s theory of political representation, which includes four dimensions: formal, descriptive, symbolic, and substantive representation. The findings reveal that women’s representation in Panwascam in Ponorogo Regency only reached 9.5%. Major obstacles include low pass rates in the Computer Assisted Test (CAT), lack of gender-oriented political education, and deeply rooted patriarchal cultural norms. This limited representation has also resulted in weak substantive contributions from women in the electoral oversight process. This study recommends strengthening affirmative recruitment policies, expanding political education for women, and providing robust social and institutional support to enhance women’s participation in future electoral management.